Fundamental Study on Force-Projecting Bilateral Control for Pneumatically Driven Follower Device - Daisuke Haraguchi; Rin Monden (Actuators, 2024)
This paper proposes the application of force-projecting bilateral control to a master-follower teleoperation system with pneumatic drive on the follower side and evaluates its effectiveness. The proposed method directly projects the operating force on the master side to the driving force on the follower side, eliminating the need for both position control and external force detection on the follower side, thereby solving the problem of low rigidity and response delay of a pneumatic servo system and providing highly stable sensor-less force presentation against variable environments. In this study, dynamic response analyses of a 1-DOF master-follower system were performed by numerical simulation using a linear system model, followed by experimental verification by implementing an actual system with an external force estimator. The results showed that the proposed force-projecting bilateral control has significantly higher positioning rigidity and better force control stability than the conventional force-reflecting bilateral control. A theoretical consideration was also given using the equivalent transformation of force transfer functions to provide evidence of high stability.